PENGARUH COVID-19 DARI SEGI EKONOMI TERHADAP MINAT VAKSIN MASYARAKAT BANGKA SELATAN - Rudi Hartono; Pudji Astuty (ITB Swadharma, 2021)
AbstractCases of covid-19 caused by the coronavirus (CoV) named Severe Acute Respiratory Syndrome Corona Virus 2 (SARSCOV-2). Transmission of this virus is through droplets of infected people when talking, coughing, sneezing, and through contact and touch. Delays in vaccine distribution can result in substantial mortality and morbidity as illustrated by the 2013-2014 West African Ebola epidemic which killed more than 11,000. Therefore, Covid-19 has had a major impact on public health, which also affects economic conditions and social life in Indonesia. Currently, the world is experiencing extraordinary life-changing challenges due to the Covid-19 pandemic. This research uses quantitative research because the information or data is realized in the form of numbers and analyzed based on statistical analysis. This study aims to determine the effect of the independent variable, namely the effect of the impact of Covid-19, the dependent variable, namely the willingness/desire for vaccination, thus it can be interpreted that the relationship between the impact of COVID-19 and the willingness to vaccinate in the community of South Bangka